Conscious and unconscious perception of pitch shifts in auditory feedback during vocalization: Behavioral functions and event-related potential correlates - Suchý, Daniel; Behroozmand, Roozbeh; Railo, Henry (Elsevier, 2025)
During vocalization, mismatches between expected and perceived auditory feedback are processed rapidly and automatically, suggesting that feedback control of vocalization operates unconsciously. However, whether consciousness modulates speech feedback control remains little studied. To address this question, we concurrently measured behavioral vocal responses and electroencephalography (EEG) in 30 participants while they vocalized and their auditory feedback was perturbed with individually calibrated perceptual threshold level pitch shifts. Following each vocalization trial, participants rated if they consciously detected a pitch shift in their auditory feedback. We analyzed the data on a trial-by-trial basis to test if vocal responses to pitch perturbations were modulated by conscious perception. Our results revealed that even on trials where the participants reported not noticing the pitch shift at all, a compensatory vocal response to the altered auditory feedback was generated. Conscious detection of a pitch shift was associated with an increased magnitude of vocal responses roughly 500–700 ms after the pitch shift compared to the unconscious trials. Conscious detection of the pitch shift correlated with early (Auditory awareness negativity, AAN) and late (Late positivity, LP) neural responses as indexed by the modulation of event-related potentials (ERPs). Source localization of the ERPs suggested that conscious pitch shift detection was associated with increased neural activity within the temporal, frontal and parietal cortical networks known to be involved in speech motor control. These findings emphasize the importance of investigating the role of consciousness in regulating speech feedback control, and their effect on the underlying neural and behavioral functions.